Avaliação da composição química, dos compostos bioativos e da atividade antioxidante em seis espécies de flores comestíveis - Vieira, Patrícia Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse para emprego alimentício em escala As flores comestíveis têm despertado interesse...

Edible flowers have attracted interest for use in food worldwide, especially after studies conducted in some countries led to the discovery and isolation of substances with antioxidant activity. In addition, its wide applicability cooking in salads, sandwiches, soups, jellies, jams, fillings, drinks and infusions, are increasingly attracting interest in the subject. However, there is still little information available on their nutritional characteristics. Thus, the objectives of this study were to determine the proximate composition, mineral content, the physical and chemical characteristics, the main bioactive compounds and antioxidant activity in edible flowers: artichoke (Cynara scolymus L.), pansy (Viola tricolor L.), broccoli (Brassica oleracea L. var . italic), marigold (calendula officinalis L.), nasturtium (Tropaeolum majus L.) and cauliflower (Brassica oleracea L. var. botrytis). Three different batches of the crop in 2013 and determined the proximate composition (moisture, ash, lipids, proteins, carbohydrates, fiber, and total energy intake), minerals (calcium, sodium, phosphorus and manganese), the physico-chemical (pH, titratable acidity and total soluble solids), the bioactive compounds (ascorbic acid, carotenoids, phenolics, flavonoids and anthocyanins), the antioxidant activity [ABTS - 2,2 - azino -bis (3 - ethylbenzothiazoline) - DPPH 6- sulphonic acid and 1,1- diphenyl-2- picrilidrazil] identified and phenolic acids (gallic acid, caffeic acid, p- cumário, chlorogenic acid and ferulic acid) and flavonoids (rutin, apigenin, quercetin and kaempferol). The identification of phenolic compounds was performed by high performance liquid chromatography with diode array detector. Extracts of flowers were obtained with 70 % acetone and analyzes were performed in triplicate using the edible portion of fresh flowers... (Complete abstract click electronic access below)
Keywords: Vitamina C; Carotenoides; Flavonoides; Antioxidantes; Flores; Fenóis; Antioxidants